A103 PHENOTYPIC VARIATION IN PEDIATRIC IBD BY AGE: A MULTI-CENTRE INCEPTION COHORT STUDY OF THE CANADIAN CHILDREN IBD NETWORK. (1st March 2018) - Dhaliwal, J; Church, P; Mack, D R; Huynh, H Q; Jacobson, K; EL-MATARY, W; deBruyn, J; Otley, A; Deslandres, C; Sherlock, M; Critch, J; Bax, K; et al.
Abstract: Background: The Paris classification of pediatric IBD divides "pediatric-onset" IBD (A1, Montreal classification) into A1a (diagnosis <10 years) and A1b(≥10and< 17y). The Montreal A1 category was arbitrarily defined, but the Paris division was based on variation in spectrum of IBD localization with age, any ileal disease being uncommon prior to age 9-10y. Other variations in phenotypic spectrum with age have not been rigorously examined. Aims: To examine the variation with age of IBD type, location, severity in a large national multi-centre prospectively accrued pediatric inception cohort of new onset IBD. Methods: Patients aged <17y presenting with new onset IBD at 12 participating academic pediatric IBD centres were enrolled in an inception cohort study of the Canadian Children Inflammatory Bowel Disease Network. Baseline and longitudinal phenotypic and demographic data were collected. IBD type was diagnosed as Crohn's disease(CD), ulcerative colitis(UC), or IBD unclassified(IBDU) using clinical, endoscopic and histologic criteria. Location was based on macroscopic disease, identified by colonoscopy and MR enterography. Baseline disease activity categorized by physician global assessment and measured by PCDAI or PUCAI. Mann-Whitney and Kruskal-Wallis tests were applied as appropriate. Results: Between April 2014 and June 2017, 1146 children (median(IQR)age 13y(11–15); 57% male; CD:62%; UC:29%; IBDU:9%) were enrolled. Colon only disease (UC/IBDU or CD-colon) was the predominant IBD phenotype until diagnosis age 11y(p=0.004), with a progressive increase thereafter in the percentage children with any ileal or other small bowel CD(Figure1). In the CD cohort overall, macroscopic location was 19%L1; 27%L2; 54%L3. L2 disease predominated until age 12y(p=0.001), when both L1 and L3 (any ileal disease) became more common. In the UC cohort the extent of disease was 9% E1; 6% E2; 11% E3; 74% E4; this distribution was consistent across all ages. The male:female ratio for the entire cohort was 1.3:1, and in both UC and CD, gender distribution was similar across all ages. Among children with UC, there was no variation in PGA of disease severity (mild:22%; moderate:42%; severe:34%; fulminant:2%) by age at diagnosis. In CD overall, severity was mild:26%; moderate:44%; severe:29%; fulminant;1%, but mild-moderate disease severity predominated until age 7y(p=0.01). Conclusions: Our data confirm the predominance of colon only IBD in younger children and support the Paris designation of A1a as early onset pediatric IBD. A spectrum of disease severity at diagnosis is seen across all ages. Funding Agencies: CIHRC.H.I.L.D Foundation (Children with Intestinal and Liver Disorders)